Technical note: Evaluation of an alternative automatic heating-stirring system in the determination of in vitro ruminal dry matter digestibility of forages using the Tilley and Terry method - Julián Andrés Castillo Vargas; Gilmara Pinto Leite; Gabriela de Jesus Coelho; Tiago Costa de Araújo; Daiany Iris Gomes; Kaliandra Souza Alves; Rafael Mezzomo (Acta Scientiarum. Animal Sciences, 2023)
This study evaluated an alternative heating-stirring system in the determination of in vitro ruminal digestibility of dry matter (IVRDMD) of forages using the Tilley and Terry (TT) method. For this purpose, the IVRDMD of three forage species (Marandu, Tifton 85, and Mombasa) was determined by incubating 500 mg of each dried and ground (1 mm) forage in 50-mL rumen inoculum during 48h, followed by quantification of the incubation residue. Two heating-stirring systems were used: i) heating in a water bath at 39°C with manual stirring every two hours (i.e., traditional system); and ii) heating in an oven with controlled temperature at 39°C and automatic agitation (44 rpm; alternative system); there was no effect of the interaction between the heating-stirring system and the type of forage (p = 0.829) on the IVRDMD of forages. The type of heating-stirring system (p = 0.422) did not affect the IVRDMD of forages. Nevertheless, the IVRDMD values of Marandu grass (system i = 598.7 g kg-1 vs system ii = 599.4 g kg-1) were greater (p < 0.001) than Tifton 85 (system i = 392.1 vs g kg-1 vs system ii = 370.7 g kg-1) and Mombasa (system i = 397.4 g kg-1; system ii = 369.7 g kg-1) grasses. In conclusion, the obtained data indicate that the alternative heating-stirring system produces similar results to those obtained using the traditionally heating-stirring system during the determination of the IVRDMD of forages.